Microsomal glutathione transferase 1 controls metastasis and therapeutic response in melanoma - Jie Zhang; Zhi-wei Ye; Paramita Chakraborty; Zhenwu Luo; John Culpepper; Muhammad Aslam; Leilei Zhang; Katarina Johansson; Jesper Z. Haeggström; Jianqiang Xu; Magnus Olsson; Danyelle M. Townsend; et al. (Elsevier, 2023)
While recent targeted and immunotherapies in malignant melanoma are encouraging, most patients acquire resistance, implicating a need to identify additional drug targets to improve outcomes. Recently, attention has been given to pathways that regulate redox homeostasis, especially the lipid peroxidase pathway that protects cells against ferroptosis. Here we identify microsomal glutathione S-transferase 1 (MGST1), a non-selenium-dependent glutathione peroxidase, as highly expressed in malignant and drug resistant melanomas and as a specific determinant of metastatic spread and therapeutic sensitivity. Loss of MGST1 in mouse and human melanoma enhanced cellular oxidative stress, and diminished glycolysis, oxidative phosphorylation, and pentose phosphate pathway. Gp100 activated pmel-1 T cells killed more Mgst1 KD than control melanoma cells and KD cells were more sensitive to cytotoxic anticancer drugs and ferroptotic cell death. When compared to control, mice bearing Mgst1 KD B16 tumors had more CD8+ T cell infiltration with reduced expression of inhibitory receptors and increased cytokine response, large reduction of lung metastases and enhanced survival. Targeting MGST1 alters the redox balance and limits metastases in melanoma, enhancing the therapeutic index for chemo- and immunotherapies.